Household Energy Poverty Index for India: An analysis of inter-state differences. (September 2020) - Gupta, Srishti; Gupta, Eshita; Sarangi, Gopal K.
Abstract: The present study offers a novel approach in measuring Household Energy Poverty Index (HEPI) using National Sample Survey unit level data, employing a robust set of 15 key energy indicators representing multiple dimensions of energy and assigning weights by using principal component analysis (PCA). Grouping households into four different categories such as 'least energy poor', 'less energy poor', 'more energy poor' and 'most energy poor', it emerges from the study that more than 1/4th of total households in the country, falls under 'most energy poor' category, and 65% households in the country are in the 'more and most energy poor' groups implying the wide-scale prevalence of energy poverty in the country. In addition, analysis based on geographical spread of energy poverty reveals that eastern states and north-eastern states are more vulnerable in terms of energy poverty, hence requires strategic policy actions at all layers of governance. The HEPI can form a rigorous analytical basis for energy policy making in India – both the federal scale as well as at the state level. Highlights: HEPI is constructed for India using multi-dimensional energy poverty framework. 15 key energy indicators are used for constructing HEPI. Results indicate 65% households suffer from some form of energy poverty.